Agroeconomic evaluation of black Sigatoka resistant hybrid plantains under smallholder management systems - Lemchi, J.; Ezedinma, C.I.; Tshiunza, M.; Tenkouano, M.; Faturoti, B. (2005)
Plantain production in Sub-Saharan Africa has been seriously threatened by black Sigatoka disease since the early 1980s. The International Institute of Tropical Agriculture has succeeded in developing hybrids that are resistant to the disease, and out-yields the best landrace by about 100%. Before introducing these hybrids to the farmers, their performance at the smallholder environment has to be established. This study was carried out to assess the performance of the hybrids under farmer- managed systems, using PITA14 (a hybrid) and Agbagba (best landrace). Thirty-six farmers from nine villages were involved. Five suckers each of the varieties were planted in farmers' fields. Data were collected over a period of 22 months on the agronomy, economics, post harvest and marketing. Results show that PITA14 had reduced cropping cycle compared to the landrace. Average black Sigatoka resistant index was 96% for PITA14 against Agbagba's 48%. The mean bunch weight was 13.3kg for PITA14 and 7.0Kg for Agbagba. Eighty-three percent of the farmers harvested 124 bunches from 81 mats of PITA14, while 55% harvested 62 bunches from 52 mats of Agbagba. Each farmer obtained an equivalent of $8.62 from PITA14 and $4.33 from Agbagba. The post harvest technology attributes were ranked higher for the hybrid. The combination of disease resistance and increased yield by the hybrid is suggestive of its high adoption potential.